Development Of The Literasiku Sanggam Talawang Application As a Digital Literacy Media Based on Local Culture At 1 Mungku Baru State Elementary School - Ridwan Sidiq; Tazkiyatunnafs Elhawwa; Hendri Hendri (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Background: This research was motivated by the low level of digital literacy among elementary school students and the limited availability of digital learning media integrating the local culture of Central Kalimantan into the learning process. The development of educational technology requires innovative learning media that not only improve students’ digital literacy skills but also support the preservation of local culture through engaging, interactive, and age-appropriate learning experiences for elementary school students. Aim: Therefore, this study aimed to develop the “Literasiku Sanggam Talawang” application as a digital literacy learning Media based on the local culture of Central Kalimantan for elementary school students. Method: This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included three professional validators (media, material, and language experts), 6 classroom teachers, and 60 elementary school students from Grades I to VI at 1 Mungku Baru State Elementary School. Data collection instruments included expert validation sheets, teacher and student usability questionnaires, observation checklists, and pre-/post-test literacy assessment sheets. Result and Discussions: The results showed that the “Literasiku Sanggam Talawang” application was categorized as highly feasible, achieving an overall mean empirical score of 92.2% (90.0% from material expert, 95.0% from language expert, and 91.7% from media expert). Teacher and student responses reached 91.7% and 90.0% respectively, placing the application in the highly practical category. Furthermore, statistical analysis revealed a substantial positive shift in students’ reading competencies, with an overall mean Normalized Gain (N-Gain) score of 0.75 and an overall effectiveness rate of 75%, falling into the high effectiveness category. The offline accessibility successfully resolved infrastructural connection barriers in remote riverine environments. Conclusion: It can be concluded that the “Literasiku Sanggam Talawang” application is highly feasible, practical, and effective as an innovative medium that accelerates digital literacy while simultaneously promoting regional heritage preservation.